Implementasi Algoritma Greedy Pada Game Pacman - Pamela Hapsari Putri; Muhammad Ridlo Arifandi; Edy Hardianto Rifeni; Fakhrur Wiradhika; Rumini Rumini; Anggit Dwi Hartanto (STMIK Budi Darma, 2018)
Pacman is an arcade game developed by Namco and released in Japan on May 22, 1980. Pac-Man, which is still popular today, has also been released on other platforms such as Game Boy and SNES. The designer of this game is Toru Iwatani, who is a Namco employee. The concept of the game in the Pacman game is very simple: Players must control the Pacman character to eat all the small dots and other special objects that are in the maze without being caught by 4 ghosts. The greedy algorithm is used to find the current shortest path from the position of the ghost character to the position of the Pacman character.